Seyfert Activity and Nuclear Star Formation in the Circinus Galaxy - Maiolino, R; Krabbe, A; Thatte, N; Genzel, R (Institute of Physics Publishing, 1997)
We present high angular resolution (0".15-0".5) near infrared images and spectroscopy of the Circinus galaxy, the closest Seyfert 2 galaxy known. The data reveal a non-stellar nuclear source at 2.2 microns. The coronal line region and the hot molecular gas emission extend for 20-50 pc in the ionization cone. The data do not show evidence for a point-like concentration of dark mass; we set an upper limit of 4*10^6 Mo to the mass of a putative black hole. We find evidence for a young nuclear stellar population, with typical ages between 4*10^7 and 1.5*10^8 yrs. The luminosity of the starburst inside a few hundred pc is comparable to the intrinsic luminosity of the Seyfert nucleus, and the two of them together account for most of the observed bolometric luminosity of the galaxy. Within the central 12 pc the starburst has an age of about 7*10^7 yrs and radiates about 2% of the luminosity of the active nucleus. We discuss the implications of these results for models that have been proposed for the starburst-AGN connection.